F-Type Three-Phase Three-Level Boost Inverter - Do, Đức Trí; Ho, Minh Đức; Van, Tấn Lượng (Journal of Technical Education Science, 2023)
This study introduces a new inverter configuration called the F-Type three-level boost inverter (3L-qSBFTI). The aim of this configuration is to enhance both the voltage factor and voltage gain compared to conditional inverters. Additionally, the neutral point voltage self-balancing is performed by the switched capacitor configuration. To increase the DC-link voltage, the short-through pulse insertion technique on the F-type invertor and the impedance network by high-frequency carriers and voltage constant VST. Comparative studies, analysis, and simulation were conducted to evaluate the advantages and efficiency of the proposed inverter. The voltage gain of this new configuration is twice that of traditional inverters.